Yorick's world : science and the knowing subject - Caws, Peter (University of California Press, 1993)
Peter Caws provides a fresh and often iconoclastic treatment of some of the most vexing problems in the philosophy of science: explanation, induction, causality, evolution, discovery, artificial intelligence, and the social implications of technological rationality. Caws's work has been shaped equally by the insights of Continental philosophy and a concern with scientific practice. In these twenty-eight essays spanning more than a quarter of a century, he ranges from discussions of the work of French philosopher Gaston Bachelard, to relations between science and surrealism, to the concept of intentionality, to the limits of quantitative description. A lively mix of history, theory, speculation, and analysis, Yorick's World presents a vision of science that includes human history and social life. It will interest professional philosophers and scientists, and at the same time its directness will make it readily accessible to nontechnical readers.